THE IMPORTANCE OF SPEECH THERAPY REHABILITATION IN THE SEARCH FOR THE INDEPENDENCE OF PERSONS WITH AUTISTIC SPECTRUM DISORDERS - Cristina da Costa Santana Nicoletti, Daniella; Cantacini, Elton (Health and Society, 2021)
Speech therapy seeks to rehabilitate and improve individuals who present certain alterations related to their area, one of which is the person with Autistic Spectrum Disorder. This article aims to point out the benefits of speech therapy for autistic patients in their independence process. And through this, present the means that will help the patient to improve their communication, behavior and socialization.